2017
DOI: 10.3390/f8100387
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Container Type and Growth Medium on Seedling Growth and Root Morphology of Cyclocarya paliurus during Nursery Culture

Abstract: Abstract:As a multiple function tree species, Cyclocarya paliurus (Batal) Iljinskaja is mainly planted and managed for timber production and medical use. To improve the seed use efficiency and outplanting performance of C. paliurus, the effects of container types and growth medium on the seedling growth and root morphology of C. paliurus were investigated by using a completely randomized block experimental design with a 4 × 3 factorial arrangement during nursery culture. Both container type and growth medium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
3
13
0
1
Order By: Relevance
“…On the contrary, except for height and root-to-shoot Biomass ratio and RCD & seedlings total Biomass, which had a significant correlation at p < 0.05, there was no significant correlation (p < 0.05) between other morphological variables. Collectively, our result was closely consistent with Tian et al [46], who reported that seedling height has a highly significant positive correlation (p < 0.01) with other morphological and Biomass variables. Therefore, such correlation of morphological variables might be used to evaluate seedling quality at green house and thereby forecast its performance at field.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, except for height and root-to-shoot Biomass ratio and RCD & seedlings total Biomass, which had a significant correlation at p < 0.05, there was no significant correlation (p < 0.05) between other morphological variables. Collectively, our result was closely consistent with Tian et al [46], who reported that seedling height has a highly significant positive correlation (p < 0.01) with other morphological and Biomass variables. Therefore, such correlation of morphological variables might be used to evaluate seedling quality at green house and thereby forecast its performance at field.…”
Section: Discussionsupporting
confidence: 93%
“…If managed properly, organic waste material can be used to increase soil fertility and improve soil structure to promote root growth (Siddiqui and Akhtar 2008). Many studies have shown that root biomass (Montemurro et al 2007;Haghighi et al 2016); number of root tips (Guo et al 2016); root activity (Zhu et al 2002); and root length, surface area and volume (Guo et al 2016;Tian et al 2017) increase after the addition of organic waste. These findings are consistent with those of the current study (Figs.…”
Section: Effects Of Organic Materials Addition On Root Growthmentioning
confidence: 99%
“…In this study, sawdust substrates were up to 67% cheaper than those substrates that include peat moss and bark, due to the low cost of sawdust, being that it is a locally-produced material. Otherwise, peat increases its cost due to increases in fuel consumption related to logistics, since the peat has to be imported from other countries, mainly from the U.S.A., hence it is important to replace or gradually reduce its use [40,41].…”
Section: Costsmentioning
confidence: 99%
“…The main objective of the seedlings producers is to minimise the cost and to improve the quality of the seedlings [42]. Therefore, it is recommended that the managers of the forest nurseries use local materials in their culture media [41,43,44]. In addition, special attention should be paid to the use of simple and environmentally acceptable materials that are easily accessible to nursery producers [40,45].…”
Section: Costsmentioning
confidence: 99%